2017
DOI: 10.3390/met7090329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Sintering Temperature and Addition of Niobium and Vanadium on the Microstructure and Mechanical Properties of Microalloyed PM Steels

Abstract: In this work, the effect of the sintering temperature on the microstructure and mechanical properties of Nb-V added powder metallurgy (PM) steels was investigated. The microstructure and mechanical properties of the Nb-V added PM microalloyed steel were examined by optical microscopy, scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), optical emission spectrometer (OES), tensile and hardness tests. Results indicated that the optimal sintering temperature was 1350 • C and the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…3 (next page) reveal precipitates of different sizes. Erden [5] had investigated the precipitates behavior in low carbon microalloyed steel containing V and Nb. The results showed that both VC(N) and NbC(N) precipitate in the austenite, forming VNbC(N) precipitates when Nb-V is added to the steel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 (next page) reveal precipitates of different sizes. Erden [5] had investigated the precipitates behavior in low carbon microalloyed steel containing V and Nb. The results showed that both VC(N) and NbC(N) precipitate in the austenite, forming VNbC(N) precipitates when Nb-V is added to the steel.…”
Section: Resultsmentioning
confidence: 99%
“…It increases hardenability and improves high temperature strength [4]. PM varies greatly between metal processing technologies is a production technique [5]. Certain studies on microstructure or mechanical properties of PM steels are available in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in grain size also contributed to the% elongation of the material. In addition, the precipitates formed contributed to the increase of yield and tensile strength by different strength increasing mechanisms such as precipitation hardening, dispersion hardening and clustering hardening [5]. The increase in sintering time improves the% elongation values representing the formability.…”
Section: Experimental Studymentioning
confidence: 99%
“…As a matter of fact, there are studies supporting this result in the literature. For example, Erden [5] investigated the effect of sintering temperature on Nb-V microalloyed steel. In this study, the increase in sintering temperature contributes to the resistance up to a certain temperature, while the temperature decreases to 1400°C.…”
Section: Experimental Studymentioning
confidence: 99%